Fenomena Menyewa Peralatan Pendakian Pada Gen Z - Nadin Alsafitri; Cahyani Pooja Andara; Silvia Widya Wulan Sari; Ruth Natalia Susanti (PT. Hasba Edukasi Mandiri, 2025)
This study aims to describe the phenomenon of renting hiking equipment among Generation Z in Kudus Regency and to analyze the influence of product, place, price, and promotion aspects. The research employed a descriptive quantitative method supported by interviews with 25 respondents aged 18–25 years who had experience renting hiking equipment. Data were collected through a 15-item questionnaire using a 1–4 Likert scale and online interviews, then analyzed descriptively. The findings indicate that the product aspect is the dominant factor in rental decisions, followed by price clarity, strategic location, and digital promotion through social media. These results confirm that Gen Z’s consumption behavior tends to emphasize efficiency, flexibility, and experiential value over ownership. Overall, rental decisions reflect a shift in consumption patterns from ownership to temporary access (access-based consumption), which aligns with modern lifestyle trends.